-9 x -5

Question

Asked 11/20/2011 11:36:40 AM

Updated 8/21/2014 12:55:58 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

starbuck89|Points 37|

Question

Asked 11/20/2011 11:36:40 AM

Updated 8/21/2014 12:55:58 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Rating

3

-9 x -5 = 45

Added 11/20/2011 12:16:01 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/3/2014 2:56:11 PM]

3

(-6xy^3)(-x^3y)(-xy)

(-6x)(y^)(-x^)(y)(-x)(y)

=(-6xy^)((-x^)(y))(-x)(y)

=(-6xy^)(-x^y)(-x)(y)

=6x^y^(-x)(y)

=6x^y^(-xy)

= -6x^y^5

(-6x)(y^)(-x^)(y)(-x)(y)

=(-6xy^)((-x^)(y))(-x)(y)

=(-6xy^)(-x^y)(-x)(y)

=6x^y^(-x)(y)

=6x^y^(-xy)

= -6x^y^5

Added 8/21/2014 12:55:58 AM

This answer has been confirmed as correct and helpful.

27,204,597

questions answered

There are no comments.